A Political Economy Model of Regulation Explained Through Fuzzy Logics - Elizabeth Real Oliveira; Manuela Castro e Silva (European Regional Science Association (ERSA), 2004)
The basic problem of environmental regulation involves the government trying to induce a polluter to take socially desirable actions, which ostensibly are not in the best interest of the polluter. But the government may not always be able to precisely control the polluter. To further complicate matters the government faces a complex problem of determining exactly what level of pollution is best for society. In reality the government faces pressures from consumers and polluters. There are some important lessons to gather from the analysis of current models of regulation. One is that there are many imperfect links between the legislature and the pollution-generating process. In this case regulation may be excessively costly, may result in considerable cheating, and may result in excessive pollution. Another lesson is that legislature does not necessarily act as an efficient benevolent maximizer of social well-being. The authors intend in this paper to explain the current view of political models of regulation, analysing them for their complexity, and attempt to provide a reasonable explanation of their functioning recurring to fuzzy logics. Understanding how the browns and greens interact with the legislature and regulatory agencies can to some extent explain the current environmental regulations. The fuzzy approach, intends to allow for easier understanding of these interactions, and provide an answer for more effective decision making. Keywords: Environmental Regulation, Environmental Economics, Fuzzy Logics, Models, Pollution Control, Sustainability
Keywords: 330; Environmental Regulation; Environmental Economics; Fuzzy Logics; Models; Pollution Control; Sustainability